(untitled) (Medico Legal Update, 2019)
The aim of the study was to identify a validation of intentions toward assessments about fitness of disabled students scale in university students majoring in adapted physical activity (APA). 385 participants were selected to identify an intention toward assessment in university students majoring in APA. The use of series of exploratory factor analyses and confirmatory factor analyses were to determine structural validity and reliability of intentions toward assessments about fitness of disabled children scale in university students specializing in APA. The outcomes of the study were adequate to validate the model fit. Further, 24 questions in the questionnaire were considered as an acceptable scale and to determine the intentions toward assessments about fitness of students with disabilities in university students majoring in APA. Cronbach’s Alpha coefficients were .88, .82, .89, .80, .89, .95, and .95. Based on the results, the Intentions toward assessments about Fitness of Disabled Students (ITAFDS) scale in university students specializing in APA had a good structural validity and reliability.